2007
DOI: 10.1093/nar/gkl860
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the physicochemical properties of an amphiphilic triblock copolymers/DNA complexes and their intramuscular transfection efficiency

Abstract: Poly(ethyleneoxide)-poly(propyleneoxide)-poly(ethyleneoxide) triblock copolymer (PEO-PPO-PEO) based plasmid delivery systems are increasingly drawing attention in the field of nonviral gene transfer because of their proven in vivo transfection capability. They result from the simple association of DNA molecules with uncharged polymers. We examined the physicochemical properties of PEO-PPO-PEO/DNA mixtures, in which the PEO-PPO-PEO is Lutrol® (PEO75-PPO30-PEO75), formulated under various conditions. We found th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
37
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 41 publications
4
37
0
Order By: Relevance
“…These results are comparable with some of the research carried out with pluronics block copolymers, which have been, and continue to be, extensively explored. 34,42,43 Similar to these, as well as to other vehicles, in vitro transfection activity of lipospermines was poor (data not shown). 38,42 Delivery systems that are efficient in the skeletal muscle or skin may be used for the purpose of DNA vaccine development.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These results are comparable with some of the research carried out with pluronics block copolymers, which have been, and continue to be, extensively explored. 34,42,43 Similar to these, as well as to other vehicles, in vitro transfection activity of lipospermines was poor (data not shown). 38,42 Delivery systems that are efficient in the skeletal muscle or skin may be used for the purpose of DNA vaccine development.…”
Section: Discussionsupporting
confidence: 66%
“…Previous studies with a chemically different set of spermine derivatives used for DNA condensation have shown the formation of complexes, but not as well defined or with as regular a shape as some of the DNA particles shown in this investigation, particularly with decanoylspermine/DNA. 18,34 Influence of imaging techniques on morphological characterization of DNA complexes does not seem to be uncommon and cryo-EM emerges as that which may interfere the least. [24][25][26][27]35 The morphology of these lipospermines is likely to influence their in vivo transfection efficiency, but the correlation is not clear.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 It has been shown that PEG induces significant changes in DNA solubility and structure under given conditions. 6 DNA concentration, pH, ionic strength of the solution, and the presence of divalent metal ions have been shown to impact PEG-DNA precipitation. 6 PEGylation of synthetic polymers such as dendrimers is shown to reduce toxicity and increase biocompatibility and DNA transfection.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Dendrimers (Scheme 1) are also unique synthetic macromolecules of nanometer dimensions with a highly branched structure and globular shape with strong affinity towards DNA and RNA complexation [4][5][6][7][8][9][10]. It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that synthetic polymers induce significant changes in DNA and RNA solubility and structure under given conditions [8][9][10][11][12][13][14][15][16][17][18][19][20]. Synthetic polymers are also used to transport miRNA and siRNA in vitro [11][12][13][14][15][16][17][18][19][20][21][22][23][24]. PEGylation of synthetic polymers such as dendrimers is shown to reduce toxicity and increase biocompatibility and DNA Transfection [6,7,9].…”
Section: Introductionmentioning
confidence: 99%